Container terminal potential hinterland delimitation in a multi-port system subject to a regionalization process - Santos, Tiago A.; Guedes Soares, C. (Journal of transport geography, 2019)
This paper presents a methodology for delimiting the potential hinterland of container terminals that consists in calculating the minimum generalised costs from load centers to different container terminals, using one of a set of possible intermodal or unimodal transportation solutions. Generalised costs include transportation costs, handling costs and transit time costs. The models of the transportation infrastructure network (roads, railway lines, ports, intermodal terminals) and of transportation and handling costs are described, including the definition of nonlinear unitary transportation costs. The methodology and models are implemented in a computer code and applied in a case study focused on the characterization of container terminal potential hinterlands across the western Iberian Peninsula. The results allow the identification of the main hinterland of different terminals in a multi-port system and the analysis of the effects of intermodal terminals in promoting a regionalization process, enabling the characterization of ‘island formations’. A hinterland contestability index is proposed and used to evaluate the degree of competition between container terminals.